Preparation and characterization of epoxy/poly (Methyl Methacrylate) (PMMA) blend system with carbon based conductive fillers - Phua, Jin Luen (School of Materials Engineering, 2016)
The overall aim of this research is to access the percolation loading of carbon based conductive fillers, namely carbon black and graphene nanoplatelets in dual matrixes epoxy/PMMA blend system.